Pembuatan Biodiesel dari Minyak Jelantah dengan Bantuan Gelombang Ultrasonik - Sri Wahyu Murni; Latifah Nurrahmaningsih; Punden Fitrianti; Alex Sando; Jefry Roy James (Eksergi, 2018)
In this research, the effect of ultrasonic on the transesterification reaction of waste cooking oil to biodiesel is studied. The biodiesel production from waste cooking oil is conducted in two process stages. All reactions are conducted with the ultrasonic power of 750 watt and frequency of 20 kHz. The first stage is the esterification process that aims to reduce the free fatty acid (FFA) contents using acid catalyst. The esterification reaction is carried out in certain condition. The second stage is the production of biodiesel through transesterification using alkaline catalyst. The parameters being studied are the effect temperature and ultrasonic amplitude to the transesterification reaction. The results shows that the FFA content can be reduced to 0,77% using sulfuric acid catalyst 1% by weight of oil, methanol to oil ratio of 6:1 and a reaction time of 60 minutes. Then, the oil is converted into biodiesel using KOH catalyst. The obtained conversion is 83% with the catalyst amount of 1% by weight of oil, methanol to oil ratio of 6:1, frequency of 20 kHz, amplitude of 50%, temperature of 60oC and reaction time of 40 minutes. The biodiesel has a density of 879 kg /m3 , 5,67 cst of viscosity, flash point of 158oC, pour point of 16oC, water content 0,0642% and caloric value 8521,1 kkal/kg.